Does mothering constitute a protective factor for recovery? - Gavriel-Fried, Belle; Mestre-Bach, Gemma; Granero, Roser; Fernandez-Aranda, Fernando; Jiménez-Murcia, Susana (Journal of Behavioral Addictions, 2023)
{Resumen no disponible]
Keywords: mothering; protective factor; recovery; JCR